(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The locations, ecology and general distribution of the new for Ukraine lichenicolous fungus Marchandiobasidium aurantiacum (Lasch) Diederich & Schultheis are given in the article. The species is determined to be a parasite of the corticolous lichenes Physcia and Xanthoria.